The problem of customer retention processes practices at TM SME MITC Melaka / Nurulizza Azmi - Azmi, Nurulizza (2011)
This study is done to identify the problem that arises in Customer Retention Processes that have been practice at TM SME MITC Melaka. Thus, studying the current retention process may define and describe the problem of Customer Retention Processes in the department. In order to find the results to the study, observation and interview is being used to gather all the information. The question revolves around the Customer Retention Management Processes as medium to describe the problem. The findings reveal that the current problem towards the processes is about the budget from the company itself and from the customer participation through the retention programmed. Although customer has a good perception with TM Customer Retention Processes, the company must overcome the problem in the process in order to deliver a good retention processes to their customer from time to time.